Интеллектуальные сенсорные системы – техническая основа "Умного предприятия" цифровой экономики - Гриценко, В.И.; Тимашова, Л.А. (Управляющие системы и машины, 2017)
На использовании интеллектуальных сенсорных систем как технической основы «Умного предприятия» цифровой экономики решается одна задача создания интеллектуальных технологий, наиболее конструктивная и экономически оправданная при разработке современных цифровых систем автоматизированного управления. Для принятия управленческих решений найдены пути решения проблемы дополнительной обработки информации в системе данных определенными методами и проблемы механизмов доставки и визуализации. Предложены пути создания промежуточных программно-аппаратных средств для интегрирования ERP и АСУ ТТП. На використанні інтелектуальних сенсорних систем як технічної основи «Розумного підприємства» цифрової економіки розв’язується одна задача створення інтелектуальних технологій, найбільш конструктивна і економічно виправдана у розробці сучасних цифрових систем автоматизованого керування. Для прийняття управлінських рішень знайдено шляхи рішення проблеми додаткової обробки інформації в системі даних певними методами та проблеми механізмів доставки і візуалізації. Запропоновано шляхи створення проміжних програмно-апаратних засобів для інтегрування ERP и АСУ ТП. Using the Intelligent Sensor Systems as a technical basis for the Smart enterprise in the digital economy one of the problem how to create new intelligent technologies is solved. These new intelligent technologies turn out to be the most constructive and economically sound when developing modern digital automated management systems. For managerial decision-making based on the integration of the upper and lower level’s systems (Enterprise Resource Planning (ERP) and the Automated Control System of the Technological Process (ACS TP) the solutions are found to solve both the problem of the additional information processing in the data system using the certain method and the problem of the ways for their delivery and visualization. The necessity to create the intermediary soft hardware that will integrate ERP and ACS TP is substantiated. The ways how to do it are suggested.